Emergency department visits and disease patterns during and after the COVID-19 lockdown - Nagham Faris; Layal Hamdar; Hani Tamim; Maha Makki; Eveline Hitti (PLoS ONE, 2026)
Background The COVID-19 pandemic caused significant disruptions in healthcare systems worldwide, particularly in emergency department (ED) utilization. While much research has focused on pre-pandemic and lockdown periods, most published evidence comes from high-income settings, with fewer studies from LMICs examining the post-lockdown ED trends and diagnostic patterns. Aim This study analyzed variations in patient volumes and shifts in disease patterns among both adult and pediatric patients presenting to the ED during and after the COVID-19 lockdown at a tertiary care center in Lebanon. Methods A retrospective observational study was conducted using administrative data from the ED of a tertiary care medical center in Beirut, Lebanon. The study focused on adult and pediatric patients admitted between February 29, 2020, and April 14, 2022, and included a total of 69,870 patients, of whom 21.2% were pediatric cases. Results The average age of patients decreased significantly post-lockdown (41.7 ± 24.9 vs. 37.7 ± 25.7 years, p-value <0.001), driven by a rise in pediatric visits (from 17.4% to 23.9%, p-value <0.001) demonstrating a catch-up effect. Adult volumes recovered more slowly throughout the post-lockdown period. Pediatric visits for respiratory tracts infections, COVID-19, and ear diseases surged post-lockdown (increases ranging from 303% to 355%). Adult patients showed decreases in COVID-19 and pregnancy-related visits and significant increases in injury, poisoning, digestive system diseases, and other viral infections. Post-lockdown, ED visits shifted toward lower acuity, with reduced admission rates and a slight decrease in length of stay. Conclusion After the COVID-19 containment period, ED visits significantly increased, especially in the pediatric age group, while adult volumes recovered more slowly with distinct diagnostic shifts. These patterns in ED visits during the pandemic highlight the need for continuous ED surveillance and flexible, adaptive healthcare strategies that can rapidly scale services and adjust staffing to meet the evolving demands of both pediatric and adult populations during and after public health emergencies.